Intake of high-fructose corn syrup sweetened soft drinks, fruit drinks and apple juice is associated with prevalent arthritis in US adults, aged 20–30 years - DeChristopher, L R (Nutr Diabetes, 2016)
OBJECTIVE: There is a link between joint and gut inflammation of unknown etiology in arthritis. Existing research indicates that regular consumption of high-fructose corn syrup sweetened (HFCS) soft drinks, but not diet soft drinks, may be associated with increased risk of seropositive rheumatoid arthritis (RA) in women, independent of other dietary and lifestyle factors. One unexplored hypothesis for this association is that fructose malabsorption, due to regular consumption of excess free fructose (EFF) and HFCS, contributes to fructose reactivity in the gastrointestinal tract and intestinal in situ formation of enFruAGEs, which once absorbed, travel beyond the intestinal boundaries to other tissues and promote inflammation. In separate studies, the accumulation of advanced glycation end-products has been associated with joint inflammation in RA. Objective of this study was to assess the association between EFF beverages intake and non-age, non-wear and tear-associated arthritis in US young adults. METHODS: In this cross sectional study of 1209 adults aged 20–30y, (Nutrition and Health Examination Surveys 2003–2006) exposure variables were high EFF beverages, including HFCS sweetened soft drinks, and any combination of HFCS sweetened soft drinks, fruit drinks (FD) and apple juice, referred to as tEFF. Analyses of diet soda and diet FD were included for comparison. The outcome was self-reported arthritis. Rao Scott Ҳ(2) was used for prevalence differences and logistic regression for associations, adjusted for confounders. RESULTS: Young adults consuming any combination of high EFF beverages (tEFF) ⩾5 times/week (but not diet soda) were three times as likely to have arthritis as non/low consumers (odds ratios=3.01; p⩽0.021; 95% confidence intervals=1.20–7.59), independent of all covariates, including physical activity, other dietary factors, blood glucose and smoking. CONCLUSION: EFF beverage intake is significantly associated with arthritis in US adults aged 20–30 years, possibly due to the intestinal in situ formation of enFruAGEs.